Liquid perfluoropolyether electrolytes with enhanced ionic conductivity for lithium battery applications. (25th September 2016) - Olson, Kevin R.; Wong, Dominica H.C.; Chintapalli, Mahati; Timachova, Ksenia; Janusziewicz, Rima; Daniel, William F.M.; Mecham, Sue; Sheiko, Sergei; Balsara, Nitash P.; DeSimone, Joseph M.
Abstract: We prepared nonflammable liquid polymer electrolytes for lithium-ion batteries by mixing ethoxylated perfluoropolyethers (PFPEs) with LiN(SO2 CF3 )2 salt. Interestingly, we identified the presence of chain coupling in the PFPE polymers and their functionalized derivatives, resulting in a mixture of PFPEs with varying molecular weights. The distribution of molecular weights, along with PFPE's multiple functionalities, allows systematic manipulation of structure to enhance electrochemical and physical properties. Furthermore, the electrolytes exhibited a wide thermal stability window (5% degradation temperature >180 °C). Despite substantial increases in viscosity upon loading the PFPEs with lithium salt, the conductivity (σ ≈ 5 × 10 −5 S cm −1 at 28 °C) of the novel electrolytes was about an order of magnitude higher than that of our previously reported PFPE electrolytes. Ethoxylated derivatives of PFPE electrolytes exhibit elevated conductivity compared to non-ethoxylated derivatives, demonstrating our capability to enhance the conductive properties of the PFPE platform by attaching various functional groups to the polymer backbone. Graphical abstract: Highlights: Perfluoropolyethers are candidates for nonflammable Li-ion battery electrolytes. PFPEs interact with the fluorinated anion of lithium salts. We explored ion transport in a PFPE material with nonfluorinated ether endgroups. Chain coupling is present in this commercial PFPE product and its derivatives. Ether groups enhance ion solvation in PFPE electrolytes, boosting conductivity 10×.